The integrated development system of breakage faces power supply, training and knowledge assessment of staff of coal mines electromechanical services - Parshina, G.I.; Feshin, B.N.; Lucas, W.A. (EAI Endorsed Transactions on Energy Web, 2017)
The principles of the Internet-technologies use for ensuring operational safety of power supply of breakage faces of coal mines with a problems solution of design, training and employees' knowledge assessment of electromechanical services are considered. The technology of the coal dredging from inclined and flat layers of average and above average power assumes that at the movement of a breakage face movements of electric equipment and recalculation of the power supply schemes will be required. The new scheme of power supply is approved according to the regulations registered in safety regulation (SR) and operational regulation (OR). Approach to creation a qualitative project of power supply of a breakage face as triune issue of the power supply development of breakage faces, training and assessment of staff’s knowledge of electromechanical services of coal mines are considered and offered. The algorithms analysis of power supply schemes calculation is carried out. On condition of the qualitative scheme of power supply the probability of possible energy saving is estimated and conditions of optimization of high-quality production are defined. Research work on creation the automated system solution of the triune issue on the basis "cloud computing" use is analyzed.
Keywords: coal; mine; extraction; power supply; calculation; project; internet-training; expert; assessment; knowledge; issue; set; stream; information; automation; system